Childhood pemphigus vulgaris: case report and literature review - Gilligan, Gerardo; Marchetti, Guillermina; Panico, René; Nieva, Betiana del Valle; Arce, Hernán; Guitart, Roberto Navarro; Herrero, Mónica; Giovo, María Elsa (Journal of Oral Diagnosis, 2025)
Childhood Pemphigus Vulgaris is a rare entity, with an estimated incidence of 0.1–0.5 cases per 100,000 inhabitants per year, occurring between the ages of 13 and 19 years, with clinical and pathological features resembling those seen in adults. Clinical manifestations include the presence of flaccid, painful blisters, and secondary erosions affecting the skin and mucous membranes, particularly the oral mucosa. To date, only about 50 cases of this entity have been reported in the literature. The diagnosis relies on clinical assessment, complemented by histopathological examination and direct immunofluorescence to identify the presence of antibodies. We report the case of a 3-year-old patient with mucocutaneous lesions of 8 months duration, highlighting the clinical features, interdisciplinary diagnostic approach, and the use of rituximab as a first-line therapeutic agent in Childhood Pemphigus Vulgaris. In addition, a concise review of the literature from the past decade was conducted, focusing on the clinical characteristics of the disease presentation, with particular emphasis on oral involvement.